PEMEROLEHAN BAHASA ASING DALAM PENGAJARAN BILINGUAL UNTUK ANAK USIA DINI - Gayatri Tridinanti (Global Expert: Jurnal Bahasa dan Sastra, 2016)
The problem of this research is "how bilingual teaching in foreign language acquisition for young children?". The purpose of this study is the bilingual teaching in foreign language acquisition of children in teaching and learning in early childhood Happy Kids Palembang.The population in this study were all students of early childhood Happy Kids in Palembang. Samples taken 36 people from the class LG. This research method is descriptive qualitative method. Data obtained by observation and interviews.Based on the findings, the authors state that teachers use bilingual teaching for teaching and learning in the classroom. And it is used almost every activity they have done. In using bilingual teaching teachers use behavior directly and indirectly. They speak two languages (bilingual) at once in the form of sentences or utterances. From the data obtained in the above, it was found that teachers need only Indonesian and English as media language during the learning process. And the teachers never use their mother tongue or local language during their teaching and learning processes.From research conducted by the author revealed the importance of teaching bilingual in acquiring a foreign language in early childhood so that they have the basic foreign language skills as early as possible, broaden their knowledge of the language through conversations using simple sentences, mastery of vocabulary, sings a song in foreign language so that the child accustomed to a foreign language.Keywords : Bilingual teaching, language acquisition.